2018
DOI: 10.1074/mcp.ra118.000749
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Human Testis-specific Protein Complex TEX101-DPEP3 and Selection of Its Disrupting Antibodies

Abstract: TEX101 is a testis-specific protein expressed exclusively in male germ cells and is a validated biomarker of male infertility. Studies in mice suggest that TEX101 is a cell-surface chaperone which regulates, through protein-protein interactions, the maturation of proteins involved in spermatozoa transit and oocyte binding. Male TEX101-null mice are sterile. Here, we identified by co-immunoprecipitation-mass spectrometry the interactome of human TEX101 in testicular tissues and spermatozoa. The testis-specific … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 75 publications
6
22
0
Order By: Relevance
“…We have previously demonstrated that some high-affinity monoclonal antibodies could disrupt protein-protein interactions. 39 Likewise, our present data suggested that the N-term monoclonal antibody could interfere with binding of some ERG-interacting proteins, and that some ERG-interacting proteins (especially very large ~2,000 kDa BAF complexes and 150-260 kDa transcriptional regulators) were binding to the 251 aa region between the N-term epitope and ETS DNA-binding domain. These large proteins were probably displaced by the N-term epitope antibody and the full ERG antibody, but not by the C-term antibody.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We have previously demonstrated that some high-affinity monoclonal antibodies could disrupt protein-protein interactions. 39 Likewise, our present data suggested that the N-term monoclonal antibody could interfere with binding of some ERG-interacting proteins, and that some ERG-interacting proteins (especially very large ~2,000 kDa BAF complexes and 150-260 kDa transcriptional regulators) were binding to the 251 aa region between the N-term epitope and ETS DNA-binding domain. These large proteins were probably displaced by the N-term epitope antibody and the full ERG antibody, but not by the C-term antibody.…”
Section: Discussionsupporting
confidence: 69%
“…44 Immunoprecipitation substantially reduces sample complexity and facilitates quantification of multiple peptides per protein, thus enabling in-depth analysis of post-translational modifications and resolution of splicing isoforms. In our previous studies, IP-SRM assays have been utilized to quantify low-abundance kallikrein-related peptidases, 45 resolve protein isoforms, 46 screen for antibody clones, 47 discover the TEX101-DPEP3 protein complex, 39 and detect a low-abundance missense variant of TEX101 protein. 48 In this study, we focused on development of IP-MS and IP-SRM assays for the low-abundance TMPRSS2-ERG fusion protein, which triggers malignant transformation of prostate epithelial cells in nearly 50% of prostate cancer cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEX101 was previously shown to be essential for the production of fertilization-competent spermatozoa through maturation of ADAM 3–6 proteins in mice (9, 10, 5658). We have also recently completed a co-immunoprecipitation-mass spectrometry study on TEX101 and identified its physical interactome, including DPEP3 protein (59). Our motivation for the present study was to apply an orthogonal proteomic approach to discover TEX101-associated proteins, some of which could be proteins with weak and transient interactions and thus missed by co-immunoprecipitation.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM3 is then processed into its mature form in the epididymis. In addition, the testis-specific cell-surface dipeptidase 3 (DPEP3) has been recently identified as a TEX101-interacting partner with peptidase activity that could potentially be modulated by TEX101 function, and facilitate the cleavage of ADAM pro-domains [16]. However, the detailed molecular mechanism through which TEX101 regulates ADAM3 function in the process of spermatogenesis is largely unknown.…”
mentioning
confidence: 99%